Literature for Empowerment: Using Picture Books to Promote SDG Awareness and Reading Skills in Indonesian Junior High Schools - Hidayati, Rina; Silvhiany, Sary; Inderawati, Rita (Universitas Hamzanwadi, 2025)
This study investigates how picture books, through their visual and textual storytelling integration, can enhance reading comprehension and promote social awareness within an under-resourced English as a Foreign Language (EFL) context. Conducted at SMP Negeri 4 Jirak Jaya in South Sumatra, Indonesia, the research examines the effectiveness of picture book-based instruction in improving students’ narrative reading skills and encouraging reflection on issues such as poverty and inequality, in alignment with the Sustainable Development Goals (SDGs 1, 4, and 10). Employing a mixed-methods case study design, the study involved 13 Grade 8 students, 11 of whom were primary contributors to their families’ income and were purposefully selected as key participants. Quantitative data were collected through validated and reliable pre- and post-tests on narrative reading comprehension. Results demonstrated a statistically significant improvement in students’ reading scores, with mean scores increasing from 54.09 to 73.86 (p < .001, Cohen’s d = 5.75), indicating a large effect size. Normality tests supported the appropriateness of parametric statistical analysis. Complementing these findings, qualitative data from semi-structured interviews revealed students’ strong emotional and personal connections to the stories. Thematic analysis yielded five key themes: emotional responses, personal experiences, favorite story elements, increased motivation to study, and lessons learned. Students consistently reported that the narratives reflected their real-life experiences and responsibilities, fostering a sense of validation, motivation, and deeper engagement with social issues. These findings highlight picture books' pedagogical potential in developing reading comprehension and cultivating empathy and critical reflection among learners in marginalized educational settings.